Triblock probe-polyA-probe electrochemical interfacial engineering for the sensitive analysis of RNAi plants. Issue 11 (6th May 2022) - Zheng, Yu; Wang, Lele; Xu, Li; Li, Yan; Yang, Xue; Yang, Zhenzhou; Li, Lanying; Ding, Min; Ren, Shuzhen; Gong, Feiyan; Chang, Jinxue; Cao, Chengming; et al.
Abstract : RNA interference (RNAi) is under fast development in agriculture and brings new challenge for GMO analysis. We developed a electrochemical biosensor for the analysis of GM maize samples based on a polyA-DNA capturing probe. Ultrasensitive detection of 10 fM RNA was realized. Abstract : RNA interference (RNAi) is currently under fast development, which brings improved crop quality and new activity against pests in agriculture, by producing RNAs to specifically inhibit gene expression. This technology, in turn, creates a pressing need for sensitive and specific analytical methods of exogenous RNA molecules in genetically modified (GM) crops for safety assessment and regulation of RNAi plants and their products. In this work, we developed a novel RNA electrochemical biosensor for the analysis of GM maize samples based on a polyA-DNA capturing probe containing three DNA segments: the central polyA segment combined onto a gold electrode surface with adjustable configuration and density, and two flanking DNA probes simultaneously captured the RNA targets through hybridization. Both the assembling and hybridization capability of our probe were demonstrated, and we systematically optimized the analytical conditions. Finally, the ultrasensitive detection of 10 fM RNA was realized without any amplification processes, and the specificity was verified by analyzing non-target maize samples. Our electrochemical biosensor provided a reliable and convenient measurement strategy for RNAi safety and quality assessment, and more importantly, our PAP (probe-polyA-probe) capturing probe exhibited an innovative design for the detection of large RNA molecules with complex secondary structures.